DOES THE HALAL LABEL MEDIATE CONSUMER PURCHASING DECISIONS? - Juliana Juliana; Bahtiar Adamsah; Suci Apriliani Utami; Firman Menne; Shafinar Ismail; Qudratov Inomjon (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: To determine the influence of price levels, celebrity  endorser, halal lifestyle and the level of halal labels as an intervening variable in purchasing decisions for Kahf products in Indonesia. Method: The method used in this research is quantitative with a causality. The sample for this research consisted of 240 respondents taken using purposive sampling which was carried out from September – December 2023. The analysis tool used was Partial Least Square – Structural Equation Modeling (PLS-SEM) using the SmartPLS 3 application. Results: The results show price levels, halal lifestyle , celebrity endorsers , halal labels, and purchasing decisions for Kahf products are in the high category. Then, the price level has a positive and significant effect on purchasing decisions for Kahf products , but the level of halal lifestyle and celebrities endorser no effect. Other findings show that the halal label is able to mediate price, halal lifestyle and celebrity endorser on the decision to purchase Kahf products . Conclusion and sugession: The development of marketing strategies by companies that sell at competitive prices, a halal lifestyle, and the support of well-known celebrities can improve the image of halal products and increase the appeal of consuls.